2013
DOI: 10.3797/scipharm.1210-18
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Stability-Indicating LC Method for the Simultaneous Estimation of Levodropropizine, Chloropheniramine, Methylparaben, Propylparaben, and Levodropropizine Impurities

Abstract: A simple, fast, and efficient RP-HPLC method has been developed and validated for the simultaneous estimation of Levodropropizine, Chloropheniramine, Methylparaben, Propylparaben, and the quantification of Levodropropizine impurities in the Reswas syrup dosage form. A gradient elution method was used for the separation of all the actives and Levodropropizine impurities by using the X-Bridge C18, 150 mm × 4.6 mm, 3.5 μm column with a flow rate of 1.0 mL/min and detector wavelength at 223 nm. The mobile phase co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 1 publication
(1 reference statement)
0
6
0
Order By: Relevance
“…The proposed method was validated as per International Conference on Harmonization guidelines and US Pharmacopeia (USP) Compendia (Horacio et al, 2018; ICH, 2005; Dongala, Katakam, et al, 2019; Dongala, Katari, et al, 2019a, 2019b; Ashok, Thirupathi, Ravindra Kumar, & Jayashree, 2017; Murthy, Srinivas, Kumar, & Mukkanti, 2011; Subramanian, Katari, Dongala, & Jonnalagadda, 2020; Palakurthi, Dongala, Yalavarthi, & Anireddy, 2019; Kumar et al, 2013a, 2013b; Dongala, Katakam, et al, 2019; Dongala & Palakurthi, 2019; Dongala, Palakurthi, et al, 2019) based on the industry standard equipment.…”
Section: Resultsmentioning
confidence: 99%
“…The proposed method was validated as per International Conference on Harmonization guidelines and US Pharmacopeia (USP) Compendia (Horacio et al, 2018; ICH, 2005; Dongala, Katakam, et al, 2019; Dongala, Katari, et al, 2019a, 2019b; Ashok, Thirupathi, Ravindra Kumar, & Jayashree, 2017; Murthy, Srinivas, Kumar, & Mukkanti, 2011; Subramanian, Katari, Dongala, & Jonnalagadda, 2020; Palakurthi, Dongala, Yalavarthi, & Anireddy, 2019; Kumar et al, 2013a, 2013b; Dongala, Katakam, et al, 2019; Dongala & Palakurthi, 2019; Dongala, Palakurthi, et al, 2019) based on the industry standard equipment.…”
Section: Resultsmentioning
confidence: 99%
“…Forced degradation studies were conducted and all the parameters for doravirine, lamivudine, and tenofovir disoproxil fumarate were within the limits. Doravirine, lamivudine, and tenofovir disoproxil fumarate have shown significant sensitivity under acid, alkali, peroxide (Umamaheshwar et al, 2021), and thermal conditions (Krishna Rao et al, 2020;Kumar et al, 2013;Kumar et al, 2017;Subramanian et al, 2020). These drugs gradually undergo degradation with time and prominent degradation was observed.…”
Section: Forced Degradation Studiesmentioning
confidence: 99%
“…In the current study, we have proposed an improved and alternative quality by design-based RP-HPLC method for the simultaneous determination of carbidopa, levodopa, and their impurities with a combination of entacapone in solid oral dosage forms. The purpose of the stabilityindicating analytical method is to provide evidence on how the quality of a drug substance or drug product varies with time under the influence of various environmental factors such as temperature, humidity, and light, and to establish a retest period for the drug substance or shelf life for the drug product and recommended storage condition [17][18][19][20]. Dongala et al [21] have demonstrated the importance of stability-indicating in the pharmaceutical industry.…”
Section: Introductionmentioning
confidence: 99%